1989
DOI: 10.1159/000125240
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Follicle-Stimulating Hormone β and Common α-Subunit Messenger Ribonucleic Acid by Gonadotropin-Releasing Hormone and Estrogen in the Sheep Pituitary

Abstract: The effect of gonadotropin-releasing hormone (GnRH) and/or estradiol (E2) on pituitary messenger ribonucleic acid (mRNA) levels of luteinizing hormone β (LHβ), follicle-stimulating hormone β (FSHβ) and the common α-subunit were determined in anterior pituitary glands from ovariectomized (OVX) ewes. Hypothalamo-pituitary disconnected (HPD) ewes receiving appropriate hormonal treatment were used to assess the relative roles of GnRH and E2 in directly regulating FSHβ and α-subunit mRNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
3
13
1
Order By: Relevance
“…This decrease in FSH secretion was first noted approximately 4 h after E 2 priming, and concentrations of FSH remained low for the next 8 h. In the intact ewes, the half-life of FSH has been reported to range from 33 to 116 min [26,39,40], and although a longer half-life for FSH has been detected in OVX ewes compared with intact ewes (90 vs. 30 min) [40], the time frame for the delayed decrease in FSH is consistent with the idea of a genomic mechanism underlying the negative feedback of E 2 on secretion of FSH. If E 2 inhibited FSH secretion via nongenomic mechanisms, then the decrease would be expected in 90 min or less rather than after 4 h. Similar negative-feedback effects of E 2 on secretion of FSH have been reported previously [4,8]. A direct effect of E 2 on secretion of FSH at the pituitary gland has been demonstrated using OVX/HPD ewes maintained with GnRH pulses [4,8,10] and in cultured ovine pituitary cells [6,7].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This decrease in FSH secretion was first noted approximately 4 h after E 2 priming, and concentrations of FSH remained low for the next 8 h. In the intact ewes, the half-life of FSH has been reported to range from 33 to 116 min [26,39,40], and although a longer half-life for FSH has been detected in OVX ewes compared with intact ewes (90 vs. 30 min) [40], the time frame for the delayed decrease in FSH is consistent with the idea of a genomic mechanism underlying the negative feedback of E 2 on secretion of FSH. If E 2 inhibited FSH secretion via nongenomic mechanisms, then the decrease would be expected in 90 min or less rather than after 4 h. Similar negative-feedback effects of E 2 on secretion of FSH have been reported previously [4,8]. A direct effect of E 2 on secretion of FSH at the pituitary gland has been demonstrated using OVX/HPD ewes maintained with GnRH pulses [4,8,10] and in cultured ovine pituitary cells [6,7].…”
Section: Discussionsupporting
confidence: 72%
“…If E 2 inhibited FSH secretion via nongenomic mechanisms, then the decrease would be expected in 90 min or less rather than after 4 h. Similar negative-feedback effects of E 2 on secretion of FSH have been reported previously [4,8]. A direct effect of E 2 on secretion of FSH at the pituitary gland has been demonstrated using OVX/HPD ewes maintained with GnRH pulses [4,8,10] and in cultured ovine pituitary cells [6,7]. In both in vivo and in vitro paradigms, the decrease in secretion of FSH was accompanied by a decrease in levels of FSHb mRNA in the pituitary gland [4,8,10,12,13].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is not in agreement with the observations of a direct inhibitory action of oestradiol on the transcription of FSHsubunits genes in the sheep pituitary (McNeilly, 1988;Mercer et al, 1989). The different response of LH and FSH cells on the genistein infusion can be due to the different reproductive season investigated and/or the different mechanisms of LH and FSH synthesis and storage.…”
Section: Discussioncontrasting
confidence: 65%
“…Colin et al (1996) reported that E 2 suppressed basal activity of a human -promoter-LUC construct in the pituitaries of OVX transgenic mice, but enhanced GnRH responsiveness. We and others have also observed that E 2 potentiates GnRH stimulation of gene expression, but it is unknown whether the effect is direct or indirect (that is, increasing GnRH receptor numbers) (Mercer et al 1989, Dalkin et al 1990, Kerrigan et al 1993, Turgeon et al 1996, Kawakami & Winters 1999.…”
Section: -Subunitmentioning
confidence: 89%